STRATEGI PENGEMBANGAN USAHA INDUTRI KECIL MENENGAH BIAR MEKAR SNACK DENGAN METODE ANALYTICAL HIERARCHY PROCESS DI KELURAHAN BULOTADA'A KOTA GORONTALO - Husain, Dinda Amelia; Imran, Supriyo; Bakari, Yuliana (Universitas Negeri Gorontalo, 2023)
Bilal Mekar Snack Small and Medium Enterprise Development Strategy Using the Analytical Hierarchy Process Method. This study aims to identify the factors that influence the development of a snack business in the Bilar Mekar small and medium snack industry using the AHP method. Analyzing the Snack Food Business Development Strategy in the Bilar Mekar Snack Small and Medium Industry Using the AHP. Analysis method used is the observation method using interview questionnaires and informant documentation as a research tool. This type of research is descriptive qualitative. The analysis used in this research is the Analytical Hierarchy Process (AHP) method. The results of this study indicate that 1.) Internal factors include: Strengths in the small and medium industry of Bilar Mekar Snack, namely products that have various flavors, have regular customers, availability of raw materials. Meanwhile, the weaknesses are lack of tools, lack of human resources in marketing. External factors include: opportunities for technological development, increasing population, while threats are similar products, and changes in tastes. 2) Based on the results of the Analytical Hierarchy Process (AHP) analysis, the level of role in the HR factor is 37.6% where the strategy applied is orientation training, whereas at the product objective role level it has a percentage level of 51.50% the strategy implemented is by providing new innovations to the product, at the producer actor role level it has a percentage level of 73.6% the strategy implemented is by always monitoring the development of Small and Medium Industry companies Bilar Mekar Snack.